Blind channel estimation for the uplink of MC-CDMA systems with timing offset - WU Hai-feng; DAI Xian-hua; LIANG Jian-qing (Tongxin xuebao)
A new blind channel estimation scheme was proposed for the uplink of multicarrier code-division multiple ac-cess（MC-CDMA） systems with timing offset（TO）.The scheme can cancel TO effects on the channel estimation,and thus work well without synchronizing the system.In addition,the estimation can exploit the knowledge of the spreading sequences to accomplish a blind estimation since the spreading sequences are known for the receiver.In computer simu-lations,the new channel estimation provides a satisfactory performance.